Trade, firm selection, and industrial agglomeration - HSU, Wen-Tai (Institutional Knowledge at Singapore Management University, 2012)
We develop a model of trade and agglomeration that incorporates trade in both intermediate goods and ﬁnal goods and allows all ﬁrms to choose their locations. There are two types of labor: skilled labor, which is mobile, and unskilled labor, which is immobile. Upon choosing its factory site, a ﬁnal goods ﬁrm that is managed by skilled labor can produce these goods using local unskilled labor and a variety of intermediate goods produced by productivity-heterogeneous producers. We characterize world equilibrium and establish the conditions under which industrial agglomeration arises as a stable equilibrium outcome. We show that when the unskilled labor force is small, the role played by the selection of intermediate ﬁrms becomes less important, and trade liberalization induces dispersion. When the unskilled labor force is large and the selection eﬀect becomes inﬂuential, trade liberalization can generate non-monotonic eﬀects on industrial agglomeration. The dispersion eﬀect of trade liberalization arises when unskilled labor-intermediate input complementarity matters to ﬁrm selection to a greater degree. When this is the case, trade liberalization may induce less selective ﬁrm entry and cause average productivity to fall.